The Implication of Pathway Turn and Task Condition on Gait Quantified Using SmartWalk: Changes With Age and Parkinson’s Disease With Relevance to Postural Strategy and Risk of Fall - Pallavi, Priya; Jariwala, Neeti; Patel, Niravkumar; Kanetkar, Manasi; Diwan, Shraddha; Lahiri, Uttama (Frontiers in Neuroscience, 2022)
One’s gait can be affected by aging, pathway with turns, task demands, etc., causing changes in gait-related indices and knee flexion (influencing posture). Walking on pathways with turns threatens stability, affecting one’s gait-related indices and posture. The ability to overcome such deficits is compromised with age and neurological disorders, e.g., Parkinson’s Disease (PD) leading to falls. Also, task demands imposed by single and dual-task (e.g., counting backward while walking) conditions affect the gait of individuals using different postural strategies varying with age and neurological disorder. Existing research has investigated either the effect of the pathway with turn or task condition on one’s gait. However, none (to our knowledge) have explored the differentiated implications of the pathway with turn and task conditions on one’s gait-related indices and knee flexion while walking. Our study had two phases with 30 participants. Phase 1 had healthy adults (young and old) and Phase 2 had age and gender-matched healthy elderly and individuals with Parkinson’s disease (PD) who walked on pathways having turns under single and dual-task conditions. We analysed gait in terms of (i) gait-related indices (Phases 1 and 2) and (ii) knee flexion (Phase 2). Also, we analysed one’s counting performance during dual task. One’s gait-related indices and knee flexion were measured using a portable gait quantifier. The aim was to (i)understand whether both pathways with turn and task conditions are equally effective in affecting the gait of (a)individuals of varying ages and (b) gender-matched healthy older adults and individuals with PD, (ii)study variations of knee joint angles while walking on pathways having turns (under different task conditions) in terms of its clinical relevance, and (iii) explore the implication of pathway with turn on counting performance (with relevance to postural strategy) with varying age and PD. Results indicated that for the younger group, the task condition caused statistical variations in gait-related indices. For the older group, both pathways with turn and task conditions had statistical implications on gait-related indices. Additionally, individuals with PD demonstrated a higher variation in knee flexion than their healthy counterparts. Again, pathways with varying turns elicited variations in counting performance indicating different postural strategies being employed by the three groups.